2011
DOI: 10.1111/j.1530-0277.2011.01618.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Sialic Acid Index of Plasma Apolipoprotein J and Phosphatidylethanol During Alcohol Detoxification—A Pilot Study

Abstract: Our preliminary data suggest that SIJ and PEth might hold potential as markers of heavy ethanol intake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 64 publications
1
22
0
1
Order By: Relevance
“…In clinical studies conducted on chronic heavy drinkers, PEth was found to be detectable in blood up to 28 days after sobriety [32,4046]. In 15 alcoholics following a detoxification program, the mean half-life of blood PEth was 4.0 ± 0.7 days with a range of 3.0–5.3 days [47].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In clinical studies conducted on chronic heavy drinkers, PEth was found to be detectable in blood up to 28 days after sobriety [32,4046]. In 15 alcoholics following a detoxification program, the mean half-life of blood PEth was 4.0 ± 0.7 days with a range of 3.0–5.3 days [47].…”
Section: Resultsmentioning
confidence: 99%
“…Nine of the above-mentioned clinical trials used HPLC-ELSD for total PEth quantification in blood utilizing as an interpretative cut-off the lower limit of quantification (LOQ) of the analytical method used for PEth determination, that is: 0.22 μM [40,46,47,70,77], 0.30 μM [44,45,75] or 0.8 μM [43]. With the above-mentioned cut-offs, the diagnostic sensitivities of PEth were very high, varying from 98% [40] to 100% [4446,57].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…PEth is an alcohol marker with high sensitivity in groups with excessive alcohol consumption (96-100%) [13,14,25]. The clinical sensitivity has been more varied in groups with low or moderate alcohol consumption, largely due to differences in sensitivity between analytical methods [14,16,26,27].…”
Section: Discussionmentioning
confidence: 99%